2019
DOI: 10.4018/ijssmet.2019040101
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of an Organizational Continuum in a Japanese Accounting Cloud Service

Abstract: The purpose of this article is to clarify an organizational continuum of a technological platform development in a Japanese accounting cloud service. The authors continuously have been studying an accounting cloud service, which adopts two-sided markets structure and freemium business model. As the results, the authors obtain three findings. First, the Japanese accounting cloud service, which runs its business with regional banks in retail banking, has been exploiting its platform into partners' customers. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…On the contrary, Resmawan & Andjarwati's research showed that the factor influencing land mortgage is mortgage registration so it is necessary to modernize the mortgage registration system (Resmawan & Andjarwati, 2018). Besides, the too simplified procedure of mortgage lending by land created risks for the borrower when they become insolvent (Anderson & Kurzer, 2020;Mizuno & Odake, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Resmawan & Andjarwati's research showed that the factor influencing land mortgage is mortgage registration so it is necessary to modernize the mortgage registration system (Resmawan & Andjarwati, 2018). Besides, the too simplified procedure of mortgage lending by land created risks for the borrower when they become insolvent (Anderson & Kurzer, 2020;Mizuno & Odake, 2019).…”
Section: Introductionmentioning
confidence: 99%